Entrepreneurial Innovations, Competition and Competition Policy - Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2006)
We show that, in the case when innovations are for sale, increased product market competition, captured by reduced product market profits, can increase the incentives for innovations. The reason is that the incentive to innovate depends on the acquisition price which, in turn, might increase despite firms in the market making lower profits. We also show that stricter, but not too strict, merger and cartel policies tend to increase the incentive for innovations for sale by ensuring the bidding competition for the innovation and by increasing the relative profitability of being the most efficient firm in the industry. Moreover, it is shown that increased intensity of competition can increase the relative profitability of innovation for sale, relative to innovation for entry.
Keywords: G34; L13; L22; M13; O31; 330; Acquisitions; Entrepreneurship; Innovation; Competition; Innovation; Innovationsmanagement; Wettbewerb; Wettbewerbspolitik; Kartell; Theorie